Gagueira desenvolvimental persistente familial: disfluências e prevalência - Nogueira, Paula Roberta; Oliveira, Cristiane Moço Canhetti De; Giacheti, Célia Maria; Moretti-ferreira, Danilo (ABRAMO Associação Brasileira de Motricidade Orofacial, 2015)
Abstract:PURPOSE: to characterize and to compare the frequency of speech disfluency in adults with familial persistent developmental stuttering in males and females, the stuttering severity and then to determinate the familial prevalence and the sexual ratio of stuttering among the families members of the probands.METHODS: participants were 30 adults who stutter (ages between 18 and 53 years old), divided in two groups: one with 20 males, and the other with 10 females. Data were gathered by clinical and familial history, fluency assessment and Stuttering Severity Instrument.RESULTS: the percentages of stuttering-like disfluencies (SLD) (p=0.352), of other disfluencies (OD) (p=0.947) and of total disfluencies (TD) (p=0.522) were similar between the males and females. The participants showed a mean of 5.23% of SLD and 5.5% of OD. The mild subgroup was the prevalent among the participants (83.3%). The male families' members showed greater risk to stutter when compared to the females (p<0.001). The results of 1002 families' members showed 85 familiars with stuttering, which 53 were male and 32 female.CONCLUSIONS: there were no differences between the males and females concerning to the analyzed measures. Regarding the frequency of disfluencies the results show that around a half of total disfluencies was characterized as SLD. The subgroup of familial persistent developmental stuttering was characterized mainly as mild. The risk among relatives of affected probands was 8.5%.The familial prevalence data showed that risk that a person have to manifest stuttering when there is some familial affected was 8.5%.The sexual ratio showed stuttering affecting mainly males than females, and was 3.72:1.

Resumo:OBJETIVO: caracterizar e comparar a frequência das disfluências da fala de adultos com gagueira desenvolvimental persistente familial do sexo masculino e feminino, a severidade do distúrbio e determinar a prevalência familial e a razão entre gêneros da gagueira nos familiares dos probandos.MÉTODOS: participaram 30 adultos com gagueira (18 a 53 anos), divididos em dois grupos, sendo 20 do sexo masculino e 10 do sexo feminino. Os procedimentos realizados foram: história clínica e familial, avaliação da fluência e Instrumento de Severidade da Gagueira.RESULTADOS: as porcentagens de disfluências típicas da gagueira (p=0,352), de outras disfluências (p=0,947) e do total das disfluências (p=0,522) foram semelhantes entre os grupos masculino e feminino. A média de disfluências típicas da gagueira foi 5,23% e de outras disfluências 5,50%. O subtipo leve foi manifestado pela maioria dos participantes (83,3%). Os familiares do gênero masculino apresentaram maior risco de apresentar gagueira (p<0,001). Do total de 1002 familiares, 85 apresentaram gagueira. No total de familiares afetados (n=85), 53 eram do sexo masculino e 32 do feminino.CONCLUSÃO: não houve diferenças entre os grupos masculino e feminino nas medidas analisadas. Quanto à frequência das disfluências, aproximadamente metade do total das disfluências foi caracterizada como disfluências típicas da gagueira. O subtipo de gagueira desenvolvimental persistente familial foi caracterizado principalmente por um distúrbio classificado quanto à severidade como leve. O risco dos familiares dos probandos afetados foi de 8,5%. A gagueira afetou mais pessoas do gênero masculino em relação ao feminino, numa proporção de 3,72:1.
Familial persistent developmental stuttering: disfluencies and prevalence
Keywords: Speech Language and Hearing Sciences; Speech; Evaluation; Speech Disorders; Stuttering; Genetic; Fonoaudiologia; Fala; Avaliação; Distúrbios da Fala, Gagueira; Genética